Applications of AHP, FAHP, BWM, Entropy, and CRITIC Methods in Electrohydraulic Forming Process Parametric Evaluation for Automotive Panels Using the 1100 Aluminum Alloy Sheets - Oke, Sunday Ayoola; Okponyia, Kenechukwu Obinna; Adeyemi, Olusola (Universitas Atma Jaya Yogyakarta, 2022)
Although multicriteria selection methods are flexible and extensively used in machining, less attention has been paid to their comprehensive test performance in the electrohydraulic forming process. In this study, five new applications of multicriteria selection methods are proposed to analyze available parameters in the electrohydraulic forming process and select parameters best suited for further analysis and improvement of the process. The analyzed parameters are the stand-off distance, electrode gap, voltage, and medium, while the multicriteria methods are the AHP, FAHP, BMW, entropy, and CRITIC. The proposed methods were demonstrated on experimental data from the literature utilizing an impulse magnetizer system (walker type). For each method, the prioritized parametric results were obtained. All the methods assign the first position to the medium as a parameter with consensus on the voltage parameter has the worst (lowest) value of weights in all the methods. The weights of the medium parameter for the best results are 0.5030 (AHP method), 0.5600 (FAHP method), 0.5230 (best-worst method), 0.4090 (entropy method), and 0.5000 (CRITIC method). The worst parameter for all the methods is the voltage of 0.0320 (FAHP method). The results obtained from the proposed applications were compared with one another and found to be effective for multicriteria selection decisions. This article offers new methods to establish the parametric values of the electrohydraulic forming process for machining composites made of AA1100 sheets.